2020
DOI: 10.47602/jpsp.v5i2.245
|View full text |Cite
|
Sign up to set email alerts
|

Benefit finding in the COVID-19 pandemic: College students’ positive coping strategies

Abstract: The ability of college students to cope effectively during the COVID-19 pandemic is an ongoing concern which could have implications for a generation of students’ health and well-being. Although adaptive coping styles have been explored with reference to other large-scale crises, little is known from an empirical standpoint about whether college students are engaging in such coping strategies during the pandemic. The current study focuses on meaning-focused coping, a coping style often seen in response to sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 23 publications
1
16
0
3
Order By: Relevance
“…Despite the many negative effects of the pandemic on mental health in young people identified to date, evidence also suggests that young people’s altruistic motivations 45 46 and prosocial behaviours have increased, including providing practical support to others and donating to charities. 47 It is encouraging that some participants in this study reported feeling more able to talk about their mental health compared with prepandemic, suggesting less social stigma perceived by young people in this study to be associated with mental health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the many negative effects of the pandemic on mental health in young people identified to date, evidence also suggests that young people’s altruistic motivations 45 46 and prosocial behaviours have increased, including providing practical support to others and donating to charities. 47 It is encouraging that some participants in this study reported feeling more able to talk about their mental health compared with prepandemic, suggesting less social stigma perceived by young people in this study to be associated with mental health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…El estudio encontró que las estrategias de afrontamiento predicen el bienestar psicológico. Esto confirma el hallazgo de las investigaciones sobre el efecto del afrontamiento en distintas dimensiones del bienestar durante la pandemia (August & Dapkewicz, 2021;Genç & Arslan, 2021;Jacobs et al, 2021;Zacher & Rudolph, 2021). En este estudio, las estrategias de mayor impacto al bienestar fueron la aceptación y crecimiento personal, búsqueda de apoyo social, consumo de alcohol o drogas, centrarse en las emociones y desahogarse, negación, y asumir una actitud pasiva ante el afrontamiento.…”
Section: Discussionunclassified
“…Asimismo, en una investigación con estudiantes universitarios de la Florida, se encontró una relación significativa entre el uso de estrategias de afrontamiento y bienestar emocional (Jacobs et al, 2021). Los estudiantes que emplean estrategias de afrontamiento positivas, especialmente encontrar el beneficio a la situación de crisis, generalmente presentan menos discurso de miedo, ansiedad y estrés (August & Dapkewicz, 2021). De igual forma, una investigación con estudiantes filipinos encontró una correlación positiva entre las estrategias de afrotamiento de acercamiento (positivas) y el bienestar en tres dimensiones (bienestar académico, social y mental); mientras que encontró una correlación negativa entre las estrategias de afrontamiento evitativas (negativas) y el bienestar académico (Valladolid, 2021).…”
Section: Estrategias De Afrontamientounclassified
“…Although this may lead in some cases to the legitimation of violence, in other situations it may lead to civic engagement and social advocacy (26,48), two important means by which adolescents can contribute non-violently to their development and society (23). The COVID-19 pandemic represents a significant adverse event and hardship for young people which is likely to elicit a quest for meaning (49), but the role of a search for a meaning in life on young people's support for VR during the pandemic has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%